2017
DOI: 10.1007/s10288-017-0341-7
|View full text |Cite
|
Sign up to set email alerts
|

Competitive multi-agent scheduling with an iterative selection rule

Abstract: In this work we address a class of deterministic scheduling problems in which k agents compete for the usage of a single machine. The agents have their own objective functions and submit their tasks in successive steps to an external coordination subject, who sequences them by selecting the shortest task in each step. We look at the problem in two different settings and consider different combinations of cost functions. In a centralized perspective, generalizing previous results for the case with k = 2 agents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In the same research work, a new approach has been demonstrated, where the items can be shared between neighbors, only when at least one of an item's neighbors is also picked, based on asking whether that item can be chosen [17]. Further approaches have been researched, as discussed by [18], which integrates the knapsack problem with agent payoff functions to facilitate effective negotia-tions among the agents involved. Furthermore, [19] emphasizes the adoption of a bounded knapsack model, where agents base their decision making on current local data.…”
Section: State Of the Artmentioning
confidence: 99%
“…In the same research work, a new approach has been demonstrated, where the items can be shared between neighbors, only when at least one of an item's neighbors is also picked, based on asking whether that item can be chosen [17]. Further approaches have been researched, as discussed by [18], which integrates the knapsack problem with agent payoff functions to facilitate effective negotia-tions among the agents involved. Furthermore, [19] emphasizes the adoption of a bounded knapsack model, where agents base their decision making on current local data.…”
Section: State Of the Artmentioning
confidence: 99%